Psychophysiological Synchrony During Verbal Interaction in Romantic Relationships. Issue 3 (10th June 2018) - Coutinho, Joana; Oliveira‐Silva, Patrícia; Fernandes, Eugénia; Gonçalves, Oscar F.; Correia, Diogo; Perrone Mc‐Govern, Kristin; Tschacher, Wolfgang
Abstract : Previous studies about romantic relationships have shown that the reciprocal influence between partners occurs not only at the behavioral and socio‐emotional levels, but also at the psychophysiological level. This reciprocal influence is expressed in a pattern of physiological synchrony between partners (i.e., coordinated dynamics of the physiological time series). The main aim of the present study was to explore the presence of a pattern of physiological synchrony in electrodermal activity (EDA) during a couple interaction task. A second objective was to compare the synchrony levels during a negative interaction condition versus a positive interaction condition. Finally, we analyzed the association between synchrony and self‐perception of empathy, dyadic empathy, and relationship satisfaction. Thirty‐two couples (64 individuals) participated in this study. Each couple performed a structured interaction task while the EDA of both partners was being registered. The quantification of synchrony was based on the cross‐correlation of both members' EDA time‐series. In order to control for coincidental synchrony, surrogate datasets were created by repeatedly shuffling the original data of spouses X and Y of a dyad and computing synchronies on the basis of the shuffled data (pseudosynchrony values). Our results confirmed the presence of significant EDA synchrony during the interaction. We also found that synchrony was higher during the negative interactions relative to the positive interactions. Additionally, physiological synchrony during positive interaction was higher for those couples in which males scored higher in dyadic empathy. The clinical implications of these findings are discussed. Abstract : Estudios anteriores acerca de las relaciones amorosas han demostrado que la influencia recíproca entre las parejas no solo ocurre en los niveles conductuales y socioemocionales, sino también en el nivel psicofisiológico. Esta influencia recíproca se expresa en un patrón de sincronía fisiológica entre los integrantes de la pareja (p. ej.: la dinámica coordinada de las series temporales fisiológicas). El objetivo principal del presente estudio fue analizar la presencia de un patrón de sincronía fisiológica en la actividad electrodérmica (AED) durante una tarea de interacción de la pareja. Un segundo objetivo fue comparar los niveles de sincronía durante una situación de interacción negativa frente a una situación de interacción positiva. Finalmente, analizamos la asociación entre la sincronía y la autopercepción de empatía, la empatía diádica y la satisfacción con la relación. Treinta y dos parejas (64 personas) participaron en este estudio. Cada pareja llevó a cabo una tarea de interacción estructurada mientras se registraba la AED de ambos integrantes de la pareja. La cuantificación de la sincronía se basó en la correlación cruzada de las series temporales de la AED de ambos miembros. A fin de controlar la sincronía simultánea, se crearon conjuntos de datos sustitutos entremezclando continuamente los datos originales de los cónyuges X e Y de una díada y computando las sincronías sobre la base de los datos mezclados (valores de seudosincronía). Nuestros resultados confirmaron la presencia de una sincronía considerable de la AED durante la interacción. También descubrimos que la sincronía fue mayor durante las interacciones negativas respecto de las interacciones positivas. Además, la sincronía fisiológica durante la interacción positiva fue mayor en aquellas parejas en las cuales los hombres obtuvieron un puntaje más alto en la empatía diádica. Se debaten las consencuencias clínicas de estos resultados. Abstract : 以往关于恋爱关系的研究表明伴侣间相互影响不仅发生在行为和社会情感层面, 而且发生在心里社会层面。这种相互影响表现在伴侣间生理同步性(例如生理时间协调动态性)。该研究的主要目的是探讨伴侣互动活动过程中皮电活动生理同步性模式 。第二个目的是比较消极互动情况下和积极互动情况下同步性水平。最后我们分析了同步性, 移情自我感知, 二元移情, 以及关系满意度之间的关联。32对伴侣(64个个人)参与了这项研究。每对伴侣完成一项结构性互动活动过程中伴侣双方EDA被记录下来。同步性定量分析基于伴侣双方EDA时间序列相互关联。为了控制巧合同步性, 我们通过重复洗牌伴侣X和伴侣Y的原始数据以及在洗牌过的数据(虚拟同步性值)基础上计算同步性创建了代理数据库。我们的研究结果证实了伴侣互动过程中明显EDA同步性的存在。我们还发现消极互动中同步性比积极互动中高。此外, 男方二元移情水平较高的伴侣中积极互动过程生理同步性也较高。我们还讨论了这些研究发现的临床意义。